Fischer–Tropsch synthesis: effect of Cu, Mn and Zn addition on activity and product selectivity of cobalt ferrite. Issue 67 (29th June 2016) - Gnanamani, Muthu Kumaran; Hamdeh, Hussein H.; Jacobs, Gary; Qian, Dali; Liu, Fang; Hopps, Shelley D.; Thomas, Gerald A.; Shafer, Wilson D.; Xiao, Qunfeng; Hu, Yongfeng; Davis, Burtron H.
Abstract : The effect of Cu, Mn and Zn addition on cobalt ferrite was investigated for FT synthesis. The FT activity remains more or less the same for all four catalysts at higher temperatures. Zn and Mn were found to promote alcohol formation. Abstract : The effect of Cu, Mn and Zn addition on cobalt ferrite was investigated for Fischer–Tropsch synthesis (FTS). Oxalate co-precipitation followed by decomposition under inert conditions was used to obtain various metal containing cobalt ferrites (Co0.7 M0.3 Fe2 O4 ). The carburization of cobalt ferrite in flowing CO at 270 °C and 175 psig yielded iron carbides (χ-Fe5 C2 and ε′-Fe2.2 C) along with a bimetallic FeCo alloy. The extent of carburization was compared among Cu, Mn, and Zn doped catalysts with undoped cobalt ferrites under similar conditions. XRD and Mössbauer spectroscopy analysis of the freshly carburized samples followed by passivation revealed that carburization of cobalt ferrite did not change appreciably with addition of Cu or Mn. On the other hand, Zn was found to retard the carburization of cobalt ferrite. Analysis of the used FT catalysts suggests that Cu is less efficient over Mn and Zn in stabilizing the iron carbides ( i.e., active form of iron) during FT synthesis. The FT activity remains more or less the same for the undoped, Cu and Zn containing cobalt ferrites at higher temperatures. The CO conversion of Co0.7 Mn0.3 Fe2.0 catalyst was much lower than the other catalysts tested. Addition of Zn or Mn to cobalt ferrite was found to promote alcohol formation, particularly at higher reaction temperatures. The water–gas shift activity of the catalysts was found to decrease in the following order, Co1.0 Fe2.0 > Co0.7 Mn0.3 Fe2.0 > Co0.7 Zn0.3 Fe2.0 > Co0.7 Cu0.3 Fe2.0 .